Vitiligo associated hypoacusis: a case control study - Maheshwari, Abhishek; Panigrahi, Rajlaxmi; Mahajan, Shruti (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: Vitiligo is a progressive depigmenting cutaneous disorder, resulting from the loss of melanocytes. In the inner ear, melanocytes are believed to play an important role in development and normal functioning of stria vascularis. Acoustic abnormalities in vitiligo patients remain obscured for long durations. This study was carried out to determine the prevalence of subclinical sensorineural hearing loss in vitiligo patients, if any, in comparison with controls and to detect any relevant demographic or clinical finding characteristic of hypoacusis in vitiligo patients. Methods: A prospective case control study was undertaken in 50 vitiligo patients (case group), who were compared with another 50 age and sex matched healthy volunteers (control group). All cases underwent detailed dermatological and ENT examination and were subjected to tests like pure tone audiometry, transient evoked otoacoustic emission (TEOAE). Results: A statistically significant (p value = 0.039), higher average pure tone hearing threshold (APT-HT) was noted in vitiligo patients in comparison with the control group. Vitiligo originating at the head and neck was strongly associated with hypoacusis (54.55%, 6 of 11 cases). TEOAE reproducibility % was reduced to 42.6% in the vitiligo group. Conclusion: Vitiligo is associated with subclinical sensorineural hypoacusis. Vitiligo with its primary site in head and neck region and co-exixting leucotrichia shows a strong association with asymptomatic sensorineural hypoacusis in such patients. Pure tone audiometery and TEOAE can be effectively used to assess and follow up vitiligo patients for asymptomatic subclinical sensorineural hypoacusis.